MISOGYNY AND SEXISM IN THE ADS ON SERBIAN TELEVISIONS (Živi jezici: Journal for Foreign Languages and Literatures, 2020)
The subject of this work is misogyny and sexism in television commercials that abound in gender stereotypes. The analyzed corpus consists of advertisements broadcast in Serbia on television networks with national coverage between autumn 2018 and summer 2020. An attempt is made to explain, from a feminist point of view, with what linguistic and persuasive resources a certain degree of gender discrimination is created in television commercial videos. The objective of this work is to facilitate the evidence of the existence of misogynistic and sexist discourses and visual effects in television advertisements through a qualitative analysis of the corpus of the chosen advertisements, even when an emancipatory attitude appears to be propagated with respect to the issue. female. In addition to sexism and stereotypes, the presence of discrimination based on age and social status is analyzed. It is investigated how the language of advertisements reflects the social order and manifests typified and stereotyped social relations and whether, even when it formally affirms otherwise, it only corroborates already established gender roles. The results of the analysis prove that the advertisements have a very powerful psychological and social effect and that they create the preferred models of behavior and ideologies.
Keywords: sexism; televison commercials; feminism; gender stereotypes; gender roles; misogyny